Existence of solutions of nonlinear integrodifferential equation with nonlocal condition. (1997) - Balachandran, K.; Chandrasekaran, M.
Abstract : In this paper we prove the existence and uniqueness of local and global solutions of a nonlocal Cauchy problem for a class of integrodifferential equation. The method of semigroups and the contraction mapping principle are used to establish the results.